Clinical Applications of the Personality Assessment Inventory. - Blais, Mark A. (Taylor & Francis, 2010)
Clinical Applications of the Personality Assessment Inventory covers the various uses of a commonly employed multi-scale self-report inventory of psychological functioning. This book has€gathered leading experts in psychological assessment practice and research to describe the uses of this flexible instrument across the settings and applications for which it has been and might be used.